Effect of Aflatoxin Laced Diet on the Utero-Fallopian Tube Histology in New Zealand White Rabbits - Kitilit, Jackson K.; Magak, Gideon N.; Mwaniki, Dickson M.; Chumba, David K. (African Journal of Education,Science and Technology (AJEST), 2022)
Fungi are extremely adaptable organisms with the capacity to metabolize a large variety of substrates over a wide range of environmental conditions and are produced only under aerobic conditions. Aflatoxin contamination is promoted by stress or damage to crops due to drought prior to harvest and inadequate drying during storage. High concentrations of aflatoxins above acceptable levels are in some instances found mainly in feed grains particularly maize and groundnuts in the tropics. Aflatoxins are secondary metabolites that pose serious hazards to animal and human beings. Their severity and effect of poisoning depends on age, where younger animals are more prone than mature ones. Different sexes of particular species of animals, duration of exposure and the amount of aflatoxin being consumed cause different effects. The experimental rabbits were kept inside a housing structure which had wide windows closed with a combination of welded and chicken wire mesh to ensure free air circulation, but protected from entry of birds and predators. The house was reinforced against rodents, though rodenticides were used to check any possible presence of rats. The rabbit house was well ventilated, with sufficient light through translucent iron sheets at the roof and wide windows to ensure 12-hour light with a room temperature of 18 – 22 o C. One rabbit was picked at random from each of the four treatments to be taken to the laboratory to harvest the uterus and fallopian tubes to determine their effects following intake of aflatoxin laced feeds. At the laboratory, the rabbits were kept in air tight glass cages for 30 minutes with a piece of cotton wool that was socked with 37% formalin inside to bring them into unconscious state, meant to facilitate humane sacrificing for purposes of harvesting the structural tissues, which were there after preserved in 37% formalin solution before sectioning it for microscopy. The abdomen was opened and the uterus and fallopian tubes harvested for preparation of histological sections in readiness for microscopic examination. The organs were treated with a fixative at the ratio of 2:1 for formalin and tissue at room temperature and allowed to dry for 12 hours. The tissues were fixed, embedded in paraffin wax, sectioned, stained using hematoxylin and eosin, put onto the slides and examined using the microscope. The features of the cells in treatments 1 and 2 as observed appeared productive as indication of the uterus’ proliferative stage. There was mild focal aggregation of acute inflammatory neutrophil cells in the lamina propria in the submucosa of the endometrium of the uterus observed in treatment 2. The uteri in treatments 3 and 4 revealed marked necrosis of the lining of both the epithelium and the endometrium. Degeneration of the lining of epithelium of the uterine glands, appearing as vacuoles with mild leucocytic cell infiltration into the submucosa and lamina propria and focal necrosis of lamina epithelialis were observed. Examination of the cross-section of the fallopian tubes showed minor effects in treatments 3 and 4. These defects manifested as vacuolization of the lining of the epithelium of the endometrium. In conclusion, aflatoxin inclusion in New Zealand white rabbit diets at levels above 100 ppb has serious defects on both the uterus and fallopian tube to the extent that it may affect the reproductive function of the rabbits.